Psychological morbidity and return to work after injury: multicentre cohort study - Kendrick, Denise; Dhiman, Paula; Kellezi, Blerina; Coupland, Carol; Whitehead, Jessica; Beckett, Kate; Christie, Nicola; Sleney, Jude; Barnes, Jo; Joseph, Stephen; Morriss, Richard (Royal College of General Practitioners, 2017)
Background: The benefits of work for physical, psychological and financial wellbeing are well documented. Return to work (RTW) after unintentional injury is often delayed, and psychological morbidity may contribute to this delay. The impact of psychological morbidity on RTW after a wide range of unintentional injuries in the UK has not been adequately quantified. Aims: To quantify the role of psychological factors including anxiety, depression and post-traumatic distress on RTW following unintentional injuries. Design and Setting: Longitudinal multi-centre prospective study in Nottingham, Bristol, Leicester and Guildford, UK Method: Participants (n=273) were 16-69 year olds admitted to hospital following unintentional injury and, in paid employment prior to injury. They were surveyed at baseline, 1, 2, 4 and 12 months following injury on demographic and injury characteristics, psychological morbidity and RTW status. Associations between demographic, injury and psychological factors and RTW status were quantified using random effects logistic regression. Results: The odds of RTW reduced as depression scores one month post-injury increased (OR 0.87, 95%CI 0.79, 0.95) and as length of hospital stay increased (OR 0.91, 95%CI 0.86, 0.96). Those experiencing threatening life events following injury (OR 0.27, 95%CI 0.10, 0.72) and with higher scores on the crisis social support scale (OR 0.93, 95%CI 0.88, 0.99) had a lower odds of RTW. Multiple imputation analysis found similar results except crisis social support did not remain significant. Conclusion: Primary care professionals can identify patients at risk of delayed RTW who may benefit from management of psychological morbidity and support to RTW.